Design of a portable luminescence bio-tool for on-site analysis of heavy metals in water samples. Issue 12 (26th September 2018) - Mishra, Rupesh K.; Rhouati, Amina; Bueno, Diana; Anwar, Muhammad Waqas; Shahid, Shakir Ahmad; Sharma, Vinay; Marty, Jean Louis; Hayat, Akhtar
ABSTRACT: In this work, we report an innovative tool for heavy metal screening in water samples. This new chemiluminescent set-up screens the light generated from luminol oxidation by horseradish peroxidase (HRP) in the presence of hydrogen peroxide (H2 O2 ). The pollutant concentrations in real water samples were calculated by studying the effect of metal ions on chemiluminescence signal. Owing to its simplicity, portability and low cost, this approach presents a real alternative to classical optical methods. It is constructed with simple materials: a black box containing a cuvette and a micro-camera. When the enzymatic reaction takes place, the luminescence is captured by the camera placed in upright position. The image can be saved automatically in a computer for further analysis using a MATLAB interface. The RGB diagram is then established to determine the analyte concentrations in the tested samples. This method was successfully applied for the determination of mercury (Hg), lead (Pb) and cadmium (Cd) in lake and field water samples. In these experiments, three concentrations of each analytes were tested (5, 25 and 50 µg/L). We noted a good proportionality between the analyte concentration and the chemiluminescent detection intensity. Detection of binary and tertiary combinations of heavy metals has been also investigated. The developed biosensor showed low detection limits for the tested heavy metals: 1, 0.7 and 0.02 for Hg 2+, Pb 2+ and Cd 2+, respectively. Finally, excellent recoveries ranging from 98% to 104% were obtained for the HRP-inhibition assay.